2004
DOI: 10.1055/s-2004-829104
|View full text |Cite
|
Sign up to set email alerts
|

Selective Deoxygenation of Sulfoxides to Sulfides with Phosphites Catalyzed by Dichlorodioxomolybdenum(VI)

Abstract: Chemoselective deoxygenation of sulfoxides to sulfides was carried out by P(OPh) 3 in mild conditions catalyzed by dichlorodioxomolybdenum(VI).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
58
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 101 publications
(60 citation statements)
references
References 7 publications
2
58
0
Order By: Relevance
“…[11] General Procedure for Deoxygenation of Sulfoxides 1 with Pinacol Catalyzed by MoO 2 Cl 2 (dmf) 2 A mixture of the corresponding sulfoxide 1 (2 mmol), pinacol (472 mg, 4 mmol), and MoO 2 Cl 2 (dmf) 2 (14 mg, 0.04 mmol) was stirred at 90 °C until the sulfoxide was consumed (method A), as determined by GC-MS or TLC, or irradiated in a 10 mL sealed tube in the microwave cavity at 120 °C for 5−10 min (method B). The reaction was cooled to rt and the crude mixture was treated with 0.5 M NaOH (25 mL) and extracted with Et 2 O (3 × 20 mL).…”
Section: Moo 2 CL 2 (Dmf)mentioning
confidence: 99%
See 2 more Smart Citations
“…[11] General Procedure for Deoxygenation of Sulfoxides 1 with Pinacol Catalyzed by MoO 2 Cl 2 (dmf) 2 A mixture of the corresponding sulfoxide 1 (2 mmol), pinacol (472 mg, 4 mmol), and MoO 2 Cl 2 (dmf) 2 (14 mg, 0.04 mmol) was stirred at 90 °C until the sulfoxide was consumed (method A), as determined by GC-MS or TLC, or irradiated in a 10 mL sealed tube in the microwave cavity at 120 °C for 5−10 min (method B). The reaction was cooled to rt and the crude mixture was treated with 0.5 M NaOH (25 mL) and extracted with Et 2 O (3 × 20 mL).…”
Section: Moo 2 CL 2 (Dmf)mentioning
confidence: 99%
“…[10] In this field we have reported the first examples of the Mo-catalyzed deoxygenation of sulfoxides [11] and N-oxides, [12] as well as the reductive cyclization of nitroaromatics. [13] In those processes phosphorous(III)-based reagents were used as oxygen-acceptors.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In this field we had previously reported that dioxomolybdenum(VI) complexes, [6] which are nontoxic and inexpensive compounds, [7] are useful catalysts for the chemoselective reduction of sulfoxides [8] and N-oxides,…”
mentioning
confidence: 99%
“…The same system was explored for the reduction of nitroaromatic compounds to anilines. 5,7 (C) Aromatic and aliphatic esters were reduced to alcohols using silanes and catalytic MoO 2 Cl 2 . Imines were efficiently reduced to amines using the same system.…”
Section: Preparationmentioning
confidence: 99%